2014
DOI: 10.1155/2014/845147
|View full text |Cite
|
Sign up to set email alerts
|

Atypical EnteropathogenicEscherichia coliStrains form Biofilm on Abiotic Surfaces Regardless of Their Adherence Pattern on Cultured Epithelial Cells

Abstract: The aim of this study was to determine the capacity of biofilm formation of atypical enteropathogenic Escherichia coli (aEPEC) strains on abiotic and biotic surfaces. Ninety-one aEPEC strains, isolated from feces of children with diarrhea, were analyzed by the crystal violet (CV) assay on an abiotic surface after 24 h of incubation. aEPEC strains representing each HEp-2 cell type of adherence were analyzed after 24 h and 6, 12, and 18 days of incubation at 37°C on abiotic and cell surfaces by CFU/cm2 counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
2
17
0
9
Order By: Relevance
“…Adherence patterns in HEp-2 cells due to biofilm production were observed in the present study; but, there was no association among the three adhesion profiles -this outcome is consistent with the study by Culler et al [26]. These authors showed the ability of aEPEC strains to adhere to, and to form biofilm on, abiotic surfaces (55 isolates -60.4%); however, there was no association between the four adherence patterns and biofilm formation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Adherence patterns in HEp-2 cells due to biofilm production were observed in the present study; but, there was no association among the three adhesion profiles -this outcome is consistent with the study by Culler et al [26]. These authors showed the ability of aEPEC strains to adhere to, and to form biofilm on, abiotic surfaces (55 isolates -60.4%); however, there was no association between the four adherence patterns and biofilm formation.…”
Section: Discussionsupporting
confidence: 91%
“…The ability of EPEC isolates to form biofilm was observed in 33.8% (24/71) of isolates assessed in the present study; therefore, they are an additional virulence factor and a natural resistance mechanism in bacteria [8,26]. Biolfim is also related to bacterial persistence in infection cases, because the exopolysaccharide matrix formed in the biofilm avoids the penetration of antimicrobial agents and hinders bacterial destruction in the biofilm [32,33].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our case, we tested this effect for already developed mature biofilm; it may be more significant in initially developing biofilms, because of the inoculum effect (Corrado et al, ; Li and Ma, ; Rose et al, ). Young biofilms grown for 24 h can have 7–8 logs of CFU (Amorena et al, ; Barraud et al, ; Culler et al, ; Freitas et al, ). The more maltodextrin is present in the medium, the higher the osmolality of the solution will be (Rong et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Atypical EPEC strains have also been shown to adhere to abiotic surfaces (polystyrene and glass) 94, 95. The non-fimbrial adhesin curli and the T1P have been shown to mediate binding to these surfaces in some aEPEC at different temperatures 90, 96…”
Section: Typical and Atypical Enteropathogenic E Colimentioning
confidence: 99%